Analyzing the efficacy of outcome-based education in Kurikulum Merdeka: A literature-based perspective - Risna Risna (Universitas Pendidikan Indonesia, 2023)
This study analyzes the effectiveness of Outcome-Based Education in Kurikulum Merdeka from a literature-based perspective. Through a literature review, this effectiveness analysis method combines theoretical and practical aspects to better understand the contribution of Outcome-Based Education in Kurikulum Merdeka from a literature-based perspective. Students can improve their reading comprehension skills by developing literary skills, interpreting metaphor and symbolism, and appreciating literary style and structure. This analysis concludes that Results-Based Education in Kurikulum Merdeka when viewed from a literature-based perspective, can increase students' understanding of literary works, develop literary skills, broaden appreciation of literary diversity, and encourage creativity in writing literature. To maximize the effectiveness of Outcome-Based Education in Kurikulum Merdeka from a literature-based perspective, strong integration between literature and results-based learning, development of critical thinking skills through literature, an emphasis on appreciation of literary diversity, and an emphasis on creativity in writing literature can be implemented. Abstrak Penelitian ini menganalisis keefektifan Pendidikan Berbasis Hasil dalam Kurikulum Merdeka dari perspektif berbasis sastra. Melalui peninjauan literatur, metode analisis keefektifan ini menggabungkan aspek teoretis dan praktis untuk memberikan pemahaman yang lebih baik tentang kontribusi Pendidikan Berbasis Hasil dalam Kurikulum Merdeka dari perspektif basis sastra. Melalui pengembangan keterampilan sastra, siswa dapat meningkatkan kemampuan membaca pemahaman, menafsirkan metafora dan simbolisme, serta menghargai gaya dan struktur sastra. Analisis ini menyimpulkan bahwa Pendidikan Berbasis Hasil dalam Kurikulum Merdeka, jika dilihat dari perspektif berbasis sastra, memiliki potensi untuk meningkatkan pemahaman siswa tentang karya sastra, mengembangkan keterampilan sastra, memperluas apresiasi terhadap keanekaragaman sastra, dan mendorong kreativitas dalam menulis sastra. Untuk memaksimalkan keefektifan Pendidikan Berbasis Hasil dalam Kurikulum Merdeka dari perspektif berbasis sastra, integrasi yang kuat antara literatur dan pembelajaran berbasis hasil, pengembangan keterampilan berpikir kritis melalui sastra, penekanan pada apresiasi terhadap keanekaragaman sastra, dan penekanan pada kreativitas dalam menulis sastra dapat diimplementasikan. Kata Kunci: basis sastra; Kurikulum Merdeka; pendidikan berbasis hasil